2023
DOI: 10.1177/10946705231190867
|View full text |Cite
|
Sign up to set email alerts
|

Visual Modality of Engagement: Conceptualization, Typology of Forms, and Outcomes

Abstract: Customers proactively engage with firms’ offerings through behavioral manifestations such as brand-related social media posts, influencing other customers in online networks and, consequently, affecting brand value. With the growth of visually oriented social media platforms, interest has increased in understanding customer engagement behavior (CEB) using visual content. In this paper, we build on CEB, image acts, visual content, and communication theories to conceptualize the Visual Modality of Engagement (VM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 75 publications
0
18
0
Order By: Relevance
“…affect their disposition) toward a focal organization (Fehrer et al, 2018;Jaakkola and Alexander, 2014). A growing body of research has identified types of CEBs that emerge within particular social/external touchpoints; these include online reviews (Azer and Alexander, 2018), social media (Azer et al, 2023;Dessart et al, 2015;Dolan et al, 2019), and specific contexts, such as the COVID-19 pandemic (Azer and Alexander, 2022).…”
Section: Customer Engagement and Journeysmentioning
confidence: 99%
See 4 more Smart Citations
“…affect their disposition) toward a focal organization (Fehrer et al, 2018;Jaakkola and Alexander, 2014). A growing body of research has identified types of CEBs that emerge within particular social/external touchpoints; these include online reviews (Azer and Alexander, 2018), social media (Azer et al, 2023;Dessart et al, 2015;Dolan et al, 2019), and specific contexts, such as the COVID-19 pandemic (Azer and Alexander, 2022).…”
Section: Customer Engagement and Journeysmentioning
confidence: 99%
“…As levels of interaction increase, so does the sharing of brand-related values and content and levels of social exchange between actors (Vivek et al, 2014). Indeed, the presence of other engaged customers affects the likelihood that others will engage and maintain engagement levels, with engagement creating strong bonds between actors around, for example, learning, sharing, and endorsing activities (Alexander et al, 2018;Azer et al, 2023;Dessart et al, 2015;Fehrer et al, 2018). However, in balancing multiple parallel engagement contexts, actors may be exposed to a range of conflicting social norms and engagement contexts, which could result in role conflicts and affect individual customers' dispositions and future intentions to (dis)engage (Alexander et al, 2018).…”
Section: Understanding and Managing Engagement Journeysmentioning
confidence: 99%
See 3 more Smart Citations